Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/cbin.11229
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of grape seed procyanidin B2 against asporin mediates glycated low‐density lipoprotein induced‐cardiomyocyte apoptosis and fibrosis

Abstract: The progression of diabetic cardiomyopathy is related to cardiomyocyte dysfunction and apoptosis. Our previous studies showed that asporin (ASPN) was significantly increased in the myocardium of db/db mice through proteomics, and grape seed procyanidin B2 (GSPB2) significantly inhibited the expression of ASPN in the heart of db/db mice. We report here that ASPN played a critical role in glycated low‐density lipoproteins (gly‐LDL) induced‐cardiomyocyte apoptosis. We found that gly‐LDL upregulated ASPN expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“… 30 It has been demonstrated that ASPN in the myocardium of the db/db mice was significantly higher than that in the control mice. 31 Thus, ASPN could play an essential role in pathological cardiac remodeling. The findings suggest that LUM and ASPN may contribute to the fibrinogenesis of cardiac remodeling of ICM.…”
Section: Discussionmentioning
confidence: 99%
“… 30 It has been demonstrated that ASPN in the myocardium of the db/db mice was significantly higher than that in the control mice. 31 Thus, ASPN could play an essential role in pathological cardiac remodeling. The findings suggest that LUM and ASPN may contribute to the fibrinogenesis of cardiac remodeling of ICM.…”
Section: Discussionmentioning
confidence: 99%
“…ASPN, rstly identi ed as an extracellular secreted protein in 2001, is distinct from other class 1 SLRP family members because of its unique aspartate residues named the D-repeat (30). It has been demonstrated that ASPN in the myocardium of the db/db mice was signi cantly higher than that in the control mice (31). Thus, ASPN could play an important role in pathological cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown modulatory effects of GSPB2 with high phenolic contents of antioxidant status in diabetes. Our previous studies showed that GSPB2 has protective effects against aortic atherosclerosis, renal and pancreas impairment, and cardiomyopathy in DM (Li et al, 2020;Yin et al, 2015;Yu et al, 2012). Yin et al reported that GSPB2 was beneficial to liver lipid metabolism disorders, potentially by decreasing hepatic lipid synthesis via the AMP-activated protein kinase pathway (Yin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dimeric procyanidin B2 is one of the main components of GSPE. Our previous studies have demonstrated the antioxidant, antiapoptotic, and cardiovascular protective effects of grape seed procyanidin B2 (GSPB2) (Li et al., 2020). Moreover, Yin et al reported that GSPB2 has a positive effect on hepatic lipid metabolic disorders by reducing hepatic lipid synthesis in db/db mice (Yin et al., 2017).…”
Section: Introductionmentioning
confidence: 99%